Analyzing Positional and Temporal Variations in Worst-Case Scenario Demands in Professional Spanish Soccer - David Lobo-Triviño; Tomás García-Calvo; Jorge Polo-Tejada; Borja Sanabria-Pino; Roberto López del Campo; Fabio Nevado-Garrosa; Javier Raya-González (Journal of Functional Morphology and Kinesiology, 2025)
Objectives: This study aimed to compare the worst-case scenario (WCS; i.e., 1-min) demands, in terms of distance covered and the number of times exceeding 85% of WCS demands, across soccer playing positions and match periods. Methods: A total of 67,518 records from 380 soccer matches during the 2023/24 season of the First Spanish Division were collected. Match events were tracked using the optical tracking system ChyronHego® (TRACAB Gen5, NY, USA) and synchronized with Mediacoach software (LaLiga, Madrid, Spain). Total distance (TD), very high-speed running (VHSR), and sprint distance were considered, and all analyses were performed using linear mixed models (LMM). Results: Center-backs (CBs) exhibited significant differences (p < 0.001) in TD compared to all other positions. Regarding actions exceeding 85% of the 1-min WCS for TD, full-backs (FBs) showed significant differences compared to CBs (p < 0.001), midfielders (MDs; p < 0.001), and attacking midfielders (AMs; p < 0.001). In terms of VHSR, significant differences were observed between MDs and wingers (Ws; p < 0.05). In relation to match periods, during 15–30, CBs demonstrated significant differences compared to all other positions for actions exceeding 85% of the 1-min WCS in TD. Conclusions: These findings suggest that training protocols could be adjusted to account for specific positional demands, particularly focusing on high-speed running and sprint actions.